A descriptive study on the inspirations and experiences, of contemporary cinematographers and their visual language styles on their selected films: basis for a video documentary - Ison, Lara Eunice M.; Mata, Marco B.; Pascual, Paolo Enrino T.; Reyes, Joanna Marie T. and Tallara, Jill Alyssa M. 4 0 16; 5 (2016)
u
Thesis: (Bachelor in Mass Communication) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2